291Serum albumin levels reversed the impact of higher resting heart rate on cardiovascular mortality. (2nd September 2021) - Liu, Yiwei
Abstract: Background: Higher resting heart rate (RHR) has been proved as a risk factor for all-cause and cardiovascular disease (CVD) mortality. However, few studies discussed its synergy with other markers on mortality prediction. Our study focused on whether the impact of RHR on CVD mortality is affected by serum albumin (SA) in Japanese general population. Methods: We followed 8, 307 participants without history of CVD from a Japanese general population. We divided participants according to quartiles of RHR [Q1(<62), Q2(62-68), Q3(69-76), and Q4(>76)], then we used Cox proportional hazard model adjusting for age, gender, BMI, blood glucose, blood pressure, anti-hypertensive treatment, total cholesterol, smoking and alcohol drinking status for estimating CVD mortality. Furthermore, we stratified the participants according to median value of SA (4.4 mg/dL) to conduct subgroup analysis. Results: During a 29-year follow-up, 1, 030 deaths due to CVD were detected. Compared to Q1 group, hazard ratios [95% confidence interval] in each RHR group for CVD mortality was Q2: 0.87 [0.74-1.04], Q3: 1.01 [0.85-1.20], Q4: 0.98 [0.83-1.16]. In lower SA group, Q2: 0.90[0.72-1.13], Q3: 0.99 [0.80-1.25], Q4: 1.27 [1.03-1.58], meanwhile in higher SA group, Q2: 0.83 [0.63-1.09], Q3: 0.99 [0.77-1.29], Q4: 0.65 [0.49-0.85]. Conclusions: Higher RHR was associated with increased risk for CVD mortality in individuals with lower SA, meanwhile the reversed relationship shown in those with higher SA. Key messages: The impact of RHR on CVD mortality might be influenced by SA in a Japanese general population.